PERILAKU MEMILIH SANTRI DI KABUPATEN DEMAK DALAM PEMILIHAN GUBERNUR JAWA TENGAH 2018 - Mila Amalia; Wachid Abdulrahman (Journal of Politic and Government Studies, 2019)
The religious sentiment that occurred at the end of 2017 seemed to have an impact on the political dynamics in Indonesia, and continued in the next political year, one of which was the party of democracy in Central Java. At that time the 2018 Central Java Pilgub was motivated by a political map that tended to be nationalist-religious and scrambled for votes among the Muslim community. Santri is one of the elements of the Muslim social class. Bothsides are from among the santri, namely Taj Yasin and Ida Fauziyah. The researchers were trying todo research on santri and were aiming to determine the level of participation and voting behavior of santri in Demak Regency in the 2018 Central Java’s governor election.                    This study used a quantitative method with a descriptive type of research.. The research was located in Demak Regency with cluster random sampling technique to determine the samples, and 96 respondents were taken as samples. The data in this study are primary data and secondary data which were obtained from data collection using questionnaires and literature studies.The results showed that the level of participation of santri in Demak Regency in the 2018 Central Java’s governor election was low. The number of abstention is still high. Moreover, the behavior of selecting santri in Demak Regency in the 2018 Central Java’s governor election tended to be rational, most of them made their choices based on the candidate's vision and mission, performance, and track record. There were no influence of money politics on their political attitudes. Instead, they use their right to vote and determine their choices based of their own will.Keywords: Governor election, participation, voting behavior, money politic